Effectiveness of inactivated influenza vaccine against laboratory-confirmed influenza in elderly Chinese patients with diabetes: A test-negative design case-control study - Zhengyan Chen; Tianchi Yang (Human Vaccines & Immunotherapeutics)
Vaccination coverage for influenza among diabetic populations remains suboptimal. Various factors contribute to this low vaccination rate, with a prominent issue being skepticism among potential vaccine recipients regarding vaccine effectiveness. We conducted a retrospective test-negative case-control study among diabetic patients aged 60 years and older in Ningbo, Zhejiang Province, China, spanning for four influenza seasons from 2018–19 to 2021–22. A total of 2,204 elderly patients were tested for influenza virus nucleic acid or antigen during the study period. After applying exclusion criteria, 199 influenza-positive cases and 199 matched influenza-negative controls were included in the final analysis. Vaccine effectiveness (VE) was estimated using an unconditional multiple logistic regression model, adjusted for age, gender, household registration and underlying health status. VE was calculated as (1-odds ratio(OR)) × 100%. Overall, the adjusted VE against laboratory-confirmed influenza from inactivated influenza vaccines over the study period was 59.4% (95%CI, 36.3% to 74.4%). VE varied across seasons, with the highest observed in the 2020–21 season and the lowest in the 2019–20 season. Importantly, repeated vaccination did not diminish vaccine effectiveness (OR = 1.2; 95% CI: 0.6 to 2.5). These findings provide a robust basis for recommending annual influenza vaccination among all elderly individuals with diabetes, absent any known contraindications.